2021
DOI: 10.3390/polym13132047
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Interaction of Doxorubicin-Loaded Silk Sericin Nanocarriers with MCF-7 Breast Cancer Cells Leads to DNA Damage

Abstract: In this paper, Bombyx mori silk sericin nanocarriers with a very low size range were obtained by nanoprecipitation. Sericin nanoparticles were loaded with doxorubicin, and they were considered a promising tool for breast cancer therapy. The chemistry, structure, morphology, and size distribution of nanocarriers were investigated by Fourier transformed infrared spectroscopy (FTIR–ATR), scanning electron microscopy (SEM) and transmission electron microscopy (TEM), and dynamic light scattering (DLS). Morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Nanometric size provides numerous advantages such as better tissue penetration and significantly high cellular uptake [ 22 ]. Radu et al [ 23 ] mentioned that sericin polymeric nanoparticles showed potent properties, e.g., low toxicity due to their biodegradable nature. The present study was the first to report the synergistic activity and nanoformulation between sericin and Egyptian propolis extract.…”
Section: Resultsmentioning
confidence: 99%
“…Nanometric size provides numerous advantages such as better tissue penetration and significantly high cellular uptake [ 22 ]. Radu et al [ 23 ] mentioned that sericin polymeric nanoparticles showed potent properties, e.g., low toxicity due to their biodegradable nature. The present study was the first to report the synergistic activity and nanoformulation between sericin and Egyptian propolis extract.…”
Section: Resultsmentioning
confidence: 99%
“…To preserve a constant volume, after each sampling, 5 mL of fresh ultrapure water were added to every flask. The release efficiency ( RE ) was determined using Equation (1) [ 62 ]: …”
Section: Methodsmentioning
confidence: 99%
“…They also show greater toxicity of drugs towards cancer cells than drugs alone. 7,52,53 Some drugs, such as Naringenin (NAR) and Docetaxel (DXL), suffer from the drawbacks of poor water solubility, systemic toxicity, and slow dissolution rate. However, their anticancer efficacy is increased by using SF NPs for delivery.…”
Section: Silk Proteins In Drug-delivery Systemsmentioning
confidence: 99%